The Distribution of Surgical-Pathologic Risk Factors in Relation to Stage in Patients with Early Stage Cervical Carcinoma - Süha Özer; Taner Turan; Nuray Yüksel; Gonca Çoban; Gökhan Tulunay; Nurettin Boran; Nejat Özgül; Faruk Köse (Medical Network, 2008)
OBJECTIVE: The divergence of surgical pathologic risk factors and adjuvant radiotherapy (RT) according to the stage were examined in patients whit early stage cervical carcinoma. STUDY DESIGN: 250 patients with adequate pathologic data who had been operated with type III radical hysterectomy were reviewed. Adjuvant RT was given in high-risk patients (tumor positive surgical margin, tumor invasion of parametrium and lymph node metastasis) after RH. Patients were staged according to the 1988 FIGO criteria. Impact of stage on surgical pathologic risk factors and possibility of adjuvant RT was evaluated. RESULTS: The mean age was 53.9 years and tumor size was 30mm. 68.4% of patients was in stage IB1, 12% in IB2 and 19.6% in IIA. Pathological diagnosis was squamous cell carcinoma in 83.2% of patients. A positive correlation was identified between the stage and vaginal metastasis and stromal invasion. However stage didn't effect invasion of parametrium, lymph node metastasis, lymphovascular space invasion, tumor positive surgical margin and ratio of adjuvant RT. CONCLUSION: Stage did not clearly predict surgical pathologic risk factors, a result of uncertainty of clinical staging. Without surgery, it is impossible to determine the actual limits of the disease with the tests available at this time.